H I column density statistics of the cold neutral medium from absorption studies - vishwakarma P.K.; Dutta P. (My University, 2025)
Physical properties of the tiny scale structures in the cold neutral medium (CNM) of galaxies is a long-standing puzzle. Only a few lines of sights in our Galaxy have been studied with mixed results on the scale-invariant properties of such structures. Moreover, since these studies measure the variation of neutral hydrogen optical depth, they do not directly constrain the density structures. In this paper, we investigate the possibility of measuring the properties of density and spin temperature structures of the HI from absorption studies of HI. Our calculations show that irrespective of the thermal properties of the clouds, the scale structure of the HI column density can be estimated, whereas, HI absorption studies alone cannot shed much light on either the amplitude of the density fluctuations and their temperature structures. Detailed methodology and calculations with some fiducial examples are presented. © 2019 The Author(s).